RISPERIDONE IN SCHIZOPHRENIA - Agashe, Mohan (Medknow Publications, 1999)
Efficacy and safety of new antipsychotic agent-risperidone was evaluated in the confirmed schizophrenic patients of either sex, over 15 years of age. Of the 30 patients who entered the study, 27 completed the trial as per the protocol and only 3 dropped out, one was lost to follow up, the other was an uncooperative patient who pulled out of the trial due to moderate side effects while one patients withdrew the consent at his own free will. The significant improvements were seen in the broad range of symptoms of schizophrenia at various time points in the trial. The significant beneficial effect on negative symptoms was particularly obvious. The drug was well tolerated by most patients, and side effects, when reported, were mild. Even the extrapyramidal symptoms reported could be easily controlled with oral trihexyphenidyl hydrochloride. The exhaustive extrapyramidal symptom rating scale also did not show any worsening during risperidone therapy. The efficacy and safety profile of novel antipsychotic drug risperidone makes it a useful therapeutic agent in the broad range of patients with schizophrenia.